PENERAPAN NILAI-NILAI AKHLAK DALAM PERATURAN DAN HUKUM FORMAL (STUDI TERHADAP KODE ETIK MAHASISWA STAIN BUKITTINGGI TAHUN 2014) - Nuraisyah, Nuraisyah; Rozi, Syafwan (Alhurriyah, 2016)
Application of the students’ code of conduct is a set of processes to define the values, ideas, ideals of ethics that must be obeyed by students. To implement and achieve these objectives, the academic community issued a code of conduct regulations contained in the Chairman's decision letter No. Sti.04.1 / PP.02.3 / 299/2011 which regulates the order, dicipline and student activities in STAIN Bukittinggi. This research revealed about the objective reality of students ethics, the implementation of the students code of conduct, and measures steps and effort to guide the students’ code of conduct in STAIN Bukittinggi. This research used a combination of qualitative and quantitative approaches. Qualitatif more likely to use in-depth analysis of data, while the quantitative is limited based on the findings of the questionnaire. In these questionnaire research, the methods are combined to get the adequated and thoroughly results about the code of conduct. As this study is a combined approach, then in this case techniques of collecting data through questionnaires, interviews, and observations will be used.